Nursing Leaders as Visionaries and Enablers of Action - Sulosaari Virpi; Kosklin Ritva; De Munter Johan (Elsevier, 2023)
Objectives
The engagement of nursing leaders is critical for the future of the cancer nursing profession, quality cancer care, and the overall health care system. The field of cancer care is facing enormous challenges, requiring strong nursing leadership. Cancer nursing leadership is needed to overcome the challenges caused by workforce shortages, restricted resources, historic and ongoing under-recognition of nursing, unsafe working conditions, and unequal access to education. The aim of this article is to contribute to the discussion about how cancer nursing leaders can act as visionaries and support transformation of cancer nursing for the future.
Data Sources
Author experience, journal articles and organizational position papers were used.
Conclusion
To improve the state of cancer nursing and the working conditions of the cancer nursing workforce, nursing leadership practices need to be embraced on all governance levels in clinical practice and academia. When effective and high-quality nursing leadership is enacted, positive outcomes for people affected by cancer, nursing, and health care systems can be achieved. Cancer nursing leadership needs to be supported through nursing scholarship, influencing national and global policies and strategies and by active involvement in national and international health care management.
Implications for Nursing Practice
Nursing leadership and governance is critical to strengthening the cancer nursing workforce. Strong nursing leadership is required to realize the vision for transforming the health care systems and cancer care. Therefore, collaboration among multidisciplinary leadership, health care organizations, academic institutions, professional organizations, and policy-making structures is warranted.